Nonlinear optical imaging of two-dimensional nanomaterials - Frederico B. Sousa; Frederico B. Sousa; Lucas Lafeta; Gladystone R. Fonseca; Ana M. de Paula (Frontiers in Nanotechnology)
Since the obtaining of graphene, two-dimensional materials have emerged as a new class of nanomaterials with a plethora of new basic properties leading to a wide range of possible applications. In particular, 2D transition metal dichalcogenides (TMDs) and hexagonal boron nitride (h-BN) have been extensively studied due to their high nonlinear optical properties. In this review, we focused on the nonlinear properties of 2D nanomaterials covering the researches that explored their nonlinearities through optical imaging of the crystal structures.